Pengaruh Karakter Komite Audit: Workload, Rotasi Auditor dan Kualitas Audit - Akbar aditiya (Journal of Social Science and Multidisciplinary Analysis, 2024)
This study aims to determine the effect of the Audit Committee Character: Workload, Auditor Rotation and Audit Quality which generally have an influence on the Audit Committee Character. This research is a type of quantitative research with a literature study approach. This article reviews the factors that influence the Audit Committee Character, namely Workload, Auditor Rotation and Audit Quality, a study of tax accounting literature. The purpose of writing this article is to build hypotheses of influence between variables to be used in further research. The results of this literature review article are: 1) Workload affects the character of the Audit Committee; 2) Auditor rotation affects the character of the Audit Committee; and 3) Audit quality affects the character of the Audit Committee